The Role of External Quality Assessments in Clinical Laboratories: Review of Their Impact on Diagnostic Accuracy and Laboratory Performance in Molecular Pathology - Alaamri, Esam Abdullah Mohammed Abdullah; Hamzi, Mustafa Ahmed Edrees; Baydi, Hafid Ahmed Mohammed; Kariri, Yasir Ibrahim Yahya; Ayashi, Hassan Mohammed Ghabesh; Y, Aqdi Ahmed Saleh; Majari, Waseem Mohammed Hadidi; Hakami, Yasir Afandi Hamed; Refaei, Majid Ahmed Abduh; Otayfi, Mohammed Ali Qasem (Journal of Ecohumanism, 2024)
External quality assessment (EQA) programs play a critical role in ensuring the accuracy and reliability of laboratory testing, particularly in the field of molecular pathology. Given the rising complexity of diagnostic tests and treatments for diseases such as cancer, robust EQA systems are essential for maintaining high standards of laboratory performance.This review examines the various types of EQA schemes implemented across clinical laboratories, focusing on their design, objectives, and impact on diagnostic accuracy. A comprehensive literature search was conducted across multiple databases, including MEDLINE, EMBASE, and CINAHL, to gather relevant studies and reports on EQA programs up to 2023.The review identifies several key findings: EQA programs significantly enhance laboratory performance by providing feedback that helps identify errors and areas for improvement. Diverse EQA schemes are tailored to different biomarkers and testing methodologies, emphasizing the importance of continuous education and training for laboratory personnel. Notably, participation in EQA programs has been associated with improved diagnostic accuracy and patient safety, particularly in oncology settings.EQA programs are indispensable for the advancement of laboratory quality assurance and the enhancement of patient care. They not only facilitate compliance with regulatory standards but also foster a culture of continuous improvement within laboratories. Future research should focus on optimizing EQA methodologies and exploring the integration of novel diagnostic technologies to further enhance laboratory performance.